2013
DOI: 10.1111/1471-0528.12407
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive use and risk of vulvodynia: a population‐based longitudinal study

Abstract: Objective To assess whether the risk of vulvodynia is associated with previous use of oral contraceptives (OCs). Design Longitudinal population-based study. Setting Four counties in south-east Michigan, USA. Population A population-based sample of women, aged 18 years and older, enrolled using random-digit dialling. Methods Enrolled women completed surveys that included information on demographic characteristics, health status, current symptoms, past and present OC use, and a validated screen for vulvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 16 publications
0
30
0
4
Order By: Relevance
“…Burrows and Goldstein 58 described a case series of 50 women who developed PVD while on HCs and who were successfully treated with topical estradiol and testosterone. However, these findings were not confirmed in two epidemiologic studies 59, 60 .…”
Section: Hormonal Factorsmentioning
confidence: 75%
“…Burrows and Goldstein 58 described a case series of 50 women who developed PVD while on HCs and who were successfully treated with topical estradiol and testosterone. However, these findings were not confirmed in two epidemiologic studies 59, 60 .…”
Section: Hormonal Factorsmentioning
confidence: 75%
“…Recent studies have shown at least four possible pathways that may modify risk of developing this disorder: (1) hormonal changes, (2) neurological changes, (3) inflammation, and (4) hypertonic pelvic floor muscles. First, evidence on the role of combined hormonal contraception (CHC) in the development of vulvodynia is inconclusive, as several cross-sectional studies have shown that CHC use significantly increases the risk of developing vulvodynia [35,36], while a recent large population-based study showed that CHC use did not increase the risk of vulvodynia [37]. Nevertheless, it has been demonstrated that CHCs induce morphologic changes in the vestibular mucosa [38] and increase its sensitivity [39].…”
Section: Biomedical Factorsmentioning
confidence: 99%
“…change in pain intensity during intercourse. It has been suggested that oral contraceptives could influence vestibular sensitivity [64] and PVD development [9] but conflicting results were found in large epidemiological studies showing a non-significant impact [65] and [66]. It was therefore decided not to exclude women taking oral contraceptives but to verify this potential confounder and if relevant, incorporate it as a covariate in the statistical model.…”
Section: Eligibility Criteriamentioning
confidence: 99%